Design and Rationale of the PRAGUE‐12 Trial: A Large, Prospective, Randomized, Multicenter Trial That Compares Cardiac Surgery With Left Atrial Surgical Ablation With Cardiac Surgery Without Ablation in Patients With Coronary and/or Valvular Heart Disease Plus Atrial Fibrillation. Issue 1 (24th December 2012) - Straka, Zbyněk; Budera, Petr; Osmančík, Pavel; Vaněk, Tomáš; Hulman, Michal; Šmíd, Michal; Malý, Marek; Widimský, Petr
Abstract Surgical ablation procedure can restore sinus rhythm (SR) in patients with atrial fibrillation (AF) undergoing cardiac surgery. However, it is not known whether it has any impact on clinical outcomes. There is a need for a randomized trial with long‐term follow‐up to study the outcome of surgical ablation in patients with coronary and/or valve disease and AF. Patients are prospectively enrolled and randomized either to group A (cardiac surgery with left atrial ablation) or group B (cardiac surgery alone). The primary efficacy outcome is the SR presence (without any AF episode) during a 24‐hour electrocardiogram after 1 year. The primary safety outcome is the combined end point of death, myocardial infarction, stroke, and renal failure at 30 days. Long‐term outcomes are a composite of total mortality, stroke, bleeding, and heart failure at 1 and 5 years. We finished the enrollment with a total of 224 patients from 3 centers in 2 countries in December 2011. Currently, the incomplete 1‐year data are available, and the patients who enrolled first will have their 5‐year visits shortly. PRAGUE‐12 is the largest study to be conducted so far comparing cardiac surgery with surgical ablation of AF to cardiac surgery without ablation in an unselected population of patients who are operated on for coronary and/or valve disease. Its long‐term results will lead to a better recognition of ablation's potential clinical benefits. The PRAGUE‐12 trial is partially funded by the Charles University Research Projects MSM0021620817 and UNCE 204010/2012. The authors have no other funding, financial relationships, or conflicts of interest to disclose.